Relationship between the Pregnant Women's Knowledge about Pregnancy Exercise and Back Pain Events at Mahdalena Pane Clinic - Fitri, Sari Rahma; Lubis, Suriati (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Back pain during pregnancy experiences pain in the back joints and ligaments to relax and is accompanied by an increase in weight The uterus changes the center of balance so that the expectant mother has to stand with her shoulders slightly pulled back. Factors that influence the occurrence of back pain are: posture, sleeping position, increased hormones, bending over, multiple pregnancies, history of pain in past pregnancies and obesity. The research methodology in this study used analytical observation with a cross sectional approach, 30 samples were purposive sampling, in Mahdalena Pane Clinic in 2021 Based on the results of research from 30 respondents with Chi-square statistical test obtained P = 0.02 < and thus Ho is rejected and Ha is accepted, namely there is a relationship between knowledge of pregnant women about pregnancy exercise with back pain (Back Pain) at the Clinic Mahdalena Pane In 2021 from the results of the research, it was found that there was no gap between theory and research (practice).